Renal sympathetic nerve activity and vascular reactivity to phenylephrine after lipopolysaccharide administration in conscious rats - Julien, Claude; Oréa, Valérie; Quintin, Luc; Piriou, Vincent; Barrès, Christian (Physiological reports, 2017)
It has been proposed that sympathoexcitation is responsible for vascular desensitization to α1‐adrenoceptor stimulation during lipopolysaccharide (LPS)‐induced systemic inflammation. The present study tested this hypothesis by examining the effects of sympatho‐deactivation with the α2‐adrenoceptor agonist, dexmedetomidine, on mean arterial pressure (MAP), renal sympathetic nerve activity (RSNA), and vascular reactivity to phenylephrine in conscious rats with cardiac autonomic blockade (methylatropine and atenolol) following LPS administration. In male, adult Sprague‐Dawley rats (n = 5 per group), RSNA and MAP were continuously recorded over 1‐h periods, before and after LPS administration (20 mg/kg iv), and finally after infusion of either saline or dexmedetomidine (5 μg/kg, then 5 μg/kg/h iv). A full dose–response curve to phenylephrine was constructed under each condition. After pooling data from both groups of rats (n = 10), LPS significantly (P = 0.005) decreased MAP (from 115 ± 1 to 107 ± 2 mmHg), increased RSNA (to 403 ± 46% of baseline values) and induced 4 to 5‐fold increases in the half‐maximal effective dose (ED50) of phenylephrine (from 1.02 ± 0.09 to 4.76 ± 0.51 μg/kg). During saline infusion, RSNA progressively decreased while vascular reactivity did not improve. Treatment with dexmedetomidine decreased MAP, returned RSNA to near pre‐endotoxemic levels, but only partially restored vascular reactivity to phenylephrine (ED50 was still threefold increased as compared with baseline values). These findings indicate that only part of the decrease in vascular reactivity to α1‐adrenoceptor stimulation during endotoxemia can be accounted for by sympathetic activation, at least on a short‐term basis. This study tested the hypothesis that sympathoexcitation is responsible for vascular desensitization to α1‐adrenoceptor stimulation during lipopolysaccharide (LPS)‐induced systemic inflammation. It was found that in conscious rats treated with LPS, only part of the decrease in vascular reactivity to α1‐adrenoceptor stimulation can be accounted for by sympathetic activation.